Faktor-Faktor Penyebab Terjadinya Infertilitas pada Pasangan Usia Subur di Desa Purwodadi Kecamatan Sunggal Tahun 2023 - Ernita Ernita; Lisdayanti Simanjuntak; Riska Susanti Pasaribu; Sonia Novita Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
AInfertility is a condition in which a person or couple is unable to achieve pregnancy after 12 months or more of regular sexual intercourse without contraception. Based on available data, the infertility rate in North Sumatra reaches 15% to 17% per year of all married couples, However, specific data on the level of infertility. This study uses a descriptive method that aims to identify the factors that cause infertility in fertile couples in Purwodadi Mulyorejo Village, Sunggal District, in 2023. The population in this study were all mothers of fertile couples who lived in Purwodadi Village, Sunggal District, in the period January-May 2023, with a total of 145 people. The sample is part of the population studied and has characteristics that are in accordance with the study. In this study, the sample used was 30 mothers of fertile couples. Of the 30 respondents who had a smoking habit, 20 people (66.7%) experienced infertility. Meanwhile, from respondents who did not smoke, as many as 10 people (33.3%) did not experience infertility. The results of the analysis showed p-value = 0.001 <α = 0.05, which means there is a significant relationship between lifestyle, especially smoking habits, and the incidence of infertility.